Analisis Faktor yang Berpengaruh terhadap Pilihan Kunjungan Pariwisata Pasar Terapung di Kota Banjarmasin - Santi, Dwi Klaudia Pebriana (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This study aims to (1) find out the dominant factor determining tourist visit to the tourismobject of Siring Tendean Floating Market and Muara Kuin Floating Market inBanjarmasin City; and (2) to know knowing the preferences of tourists on the choice ofvisits to the Siring Tendean Floating Market and Muara Kuin Floating MarketResearch respondents are five respondents who are considered to affect the developmentand development of Tourism in Banjarmasin City that can be used in the data processing.Data is processed by using AHP (Analytical Hierarchy Process).The results of this study indicate that mileage, Accommodation, and characteristics arefactors or criteria that can affect the interest of tourists and the people of BanjarmasinCity to visit the attractions of the Floating Market Siring Tendean and Muara KuinFloating Market with a reference sequence of 62% for Feature Typical, 24% forDistance, and last 14% for Accommodation. From these factors to the preferences of thechoice of tourists to the will of visits to the Floating Market Siring Tendean Ascension74% and Muara Kuin Floating Market of 26%. With the conclusion Siring TendeanFloating Market is more dominant that is equal to 74%